Control Water Loss in Your Distribution System. Issue 4 (1st April 2015) - Martin, Barb; Ries, Tom
Abstract : Taking measures to minimize water loss is a component of optimized distribution system operation. Key factors that help utilities control water loss include metering, water audits, hydraulic data collection, and leak detection.